Monitoring of mendelian genetics in rice by DNA markers - Parichart Ternchucheep (Mahidol University. Mahidol University Library and Knowledge Center, 2023)
Technology of DNA analysis, including restriction fragment length polymorphism (RFLP; and randomly amplified polymorphic DNA ((RAPD), were explored for use in rice improvement. We also tried to used RFLP assay for detecting genetic loci for fragrance and photoperiod sensitivity in Thai rice genomic DNA. Genomic DNA of KDML105 and IR36 was singly digested by 5 restriction enzymes; BamHI, EcoRI, EcoRV, HindIII, and Xbal, fractionated on agarose gel electrophoresis, blotted and later hybridized to RFLP probes. Polymorphic RFLP found were then tested for co-segragation with our two traits of interest by representative genomic DNAs F3 plants. From 31 DNA probes examined, 7 of them showed RFLPs between KDML105 and IR36 genomic DNA. Among the polymorphic RFLP probes, RG28, which was reportedly linked to fgr locus on the rice chromosome 8, revealed DNA variation in our two parental DNA digested by EcoRV, and RG445, which was mapped near Se-1 locus on the rice chromosome 6, also displayed polymorphism with two parental DNA digested by Xbal or EcoRI. With 25 representative aromatic/non-aromatic F3 plants, 89% of F3 genomic DNA from aromatic plants had the same DNA pattern as aromatic KDML105 DNA and all of non-aromatic F3 genomic DNA possessed a restrction fragment of IR36 DNA. This indicated association between the locus or RG28 and fragrance trait in Thai rice. However, RG445/ Xbal combination could not verify polymorphism between photoperiod sensitive and photoperiod insensitive characters among 14 F3 DNA samples equally selected from both photoperiod sensitive and photoperiod insensitive F(,2) lines. Additionally, RAPD assay was also explored by investigation for reaction conditions. About 193 RAPD primers was examined with KDML105 DNA. After standardization of RAPD reaction, an optimized RAPD condition for rice found was 20 ng DNA template, 0.2 uM primer, 100 nM of each dNTP, 10 mM Tris-HCI pH 8.3, 50 mM KC1, 2 mM Mgcl(,2), 0.001% gelatin and 2.0 units Taq DNA polymerase and a PCR programe of 45 cycles of 94 C DNA denaturation for I min, 36 degree C primer-DNA annealation for I min, and 72 degree C primer extension for 2 min. By the condition, 46% of 133 random RAPD primers examined could produce discrete amplified fragments with KDML105 genomic DNA.